The Impact of Intellectual Capital on Innovation in Pharmaceutical SMEs in Karachi, Pakistan - Qureshi, Ieeqan Ali (Universiti Malaysia Sarawak, (UNIMAS), 2019)
The competitive forces for pharmaceutical SMEs have changed where most of the strategies focus more on innovation and intellectual capital in order to accomplish the objective of creating competitive value. However, there were limited studies focused on intellectual capital and innovation in the context of Pakistan’s pharmaceutical SMEs. Therefore, this study focusing on investigating the intellectual capital role towards Pakistan’s pharmaceutical SMEs competitive advantage in much deeper way and particularly in the context of innovation. The research model used in this study is based on six independent variables of intellectual capital namely human capital, structural capital, customer capital, social capital, technological capital and spiritual capital that lead to SMEs innovation advantage. There were total 392 questionnaires distributed in pharmaceutical SMEs, out of which 63 percent useable questionnaires were returned. Factor analysis was used to check the reliability and validity of the constructs and multiple regression analysis was used to test the hypothesis. The study found that each of six components of intellectual capital have positive association with the innovation. However, the study also found in overall model of intellectual capital, technological capital is statistically insignificant to innovation in pharmaceutical SMEs. The results showed that the pharmaceutical SMEs in Karachi, Pakistan are less adaptive to employ technology elements in creating value that effect their competitive advantage position. Theoretically, this study takes into account the relatedness of resources and the influences of past interaction underpinning an old trajectory in the bridging of technological capital discontinuities. Particularly, this study addressed the relationship between the technological capital and innovation for investments and new capabilities development during competence-destroying change.